Hypertension Self-Care Management During COVID-19 Pandemic Crisis in the Meranao Tribe: A Phenomenological Inquiry - Jonaid M. Sadang; Sittie Inshirah P. Macaronsing; Narima M. Alawi; Normala M. Taib; Hamdoni K. Pangandaman (Jurnal Keperawatan Indonesia, 2021)
The COVID-19 crisis has been a challenging and stressful event for individuals with known underlying health problems, not to mention their higher risk of contracting the disease. This phenomenological inquiry was conducted to explore the common self-care practices of the Meranao tribe in the Province of Lanao del Sur, Philippines, concerning their management of hypertension amidst the ongoing pandemic health crisis. This study employed a descriptive-phenomenological approach. Ten known hypertensive adults participated in the study selected using purposive sampling. Data collection employed focus group discussion (FGD) and then analyzed using Colaizzi's approach. Four themes were derived which explained the common practices of the tribe in the self-care management of hypertension amidst the crisis: 1) the use of herbal remedies; 2) compliance with prescribed medications; 3) dietary control; and 4) remaining physically active. Patients’ strict compliance with known scientific self-care practices in managing hypertension forms a multidimensional strategy in controlling, managing, and preventing hypertension and its related complications. Abstrak Studi Fenomenologi tentang Praktik Manajemen Perawatan Diri pada Pasien Hipertensi Saat Pandemi COVID-19. Krisis COVID-19 telah menjadi periode yang menantang dan menegangkan bagi individu dengan riwayat masalah kesehatan, belum lagi risiko yang lebih tinggi untuk menderita penyakit tersebut. Studi fenomenologi ini bertujuan untuk mengeksplorasi praktik perawatan diri Suku Meranao di Provinsi Lanao del Sur, Filipina yang berhubungan dengan manajemen hipertensi di tengah krisis kesehatan yang sedang berlangsung. Melalui pendekatan fenomenologi deskriptif, sebanyak 10 orang dewasa penderita hipertensi bersedia untuk menjadi partisipan penelitian ini dengan menggunakan metode purposive sampling. Data diperoleh melalui focus group discussion (FGD), dan dianalisis menggunakan pendekatan Collaizi. Empat tema diperoleh untuk menjelaskan praktik mereka dalam manajemen perawatan diri hipertensi di tengah krisis: 1) penggunaan obat herbal; 2) kepatuhan terhadap obat yang diresepkan; 3) kontrol makanan, dan 4) tetap aktif secara fisik. Kepatuhan ketat pasien pada praktik perawatan diri secara ilmiah dalam manajemen hipertensi memainkan strategi multidimensi dalam kontrol, manajemen, dan pencegahan hipertensi serta komplikasi yang terkait. Kata Kunci: Filipina, hipertensi, praktik manajemen perawatan diri, riset kualitatif, suku Meranao